CDW QUANTIFICATION IN THE SEVERAL STAGES OF LIFE OF A BUILDING: IDENTIFICATION AND CHARACTERIZATION OF THE MAIN METHODS - Rodrigo Kanno; Régis Pereira Waskow; Rejane Maria Candiota Tubino (Mix Sustentável, 2020)
Construction and demolition waste (CDW) represent, in mass, the largest fraction of the waste generated in many Brazilian cities. Quantifying this type of waste is an expensive task that still has to overcome some obstacles. Lack of management and irregular disposal are some of the main limiting factors. Thus, this work aims to identify CDW quantification methods as a basis for further studies of adaptation and/or development of specific methods for the quantification of the Brazilian CDW in the different life stages of a building. Publications were identified in scientific journals and events from the set of keywords: “estimate generation”, “quantification method”, “construction and demolition waste”, “construction waste” e “demolition waste”. The articles were classified in general criteria, type of residue evaluated, scale and public interest. Therefore, it is possible to verify that there is a gap in the development of Brazilian CDW quantification methods in the various phases, which could help construction companies and public agencies to improve the management of this type of waste.